Mindsets: lived experiences of black actuarial science students - Ntombana, Sixolile (Organisational Psychology, 2026)
This qualitative study employed semi-structured interviews and an intersectionality lens to explore the experiences of six black actuarial science students at the University of Cape Town (UCT). With the underrepresentation of black African students in South Africa's actuarial science exacerbating societal imbalances, the research aims to unveil their experiences and factors shaping these students' mindsets. Mindsets are influenced by parental feedback, socioeconomic status, background, and socialisation, among other factors. At historically white UCT, challenges faced by black African actuarial science students stem from a clash between their diverse mindsets and the prevailing white-oriented academic environment. The study reveals that academic excellence and the desire to uplift families' socioeconomic status motivate students amid challenges tied to socioeconomic factors, language barriers, and disparate educational backgrounds. The mindset analysis reveals that prevalent discouragement, external expectations, and self-doubt rooted in predetermined negative beliefs foster a fixed mindset among these students. Conversely, factors fostering a growth mindset include resilience, determination, and socioeconomic motivations. Positive role models, supportive lecturers, and optimistic career prospects contribute to a growth-oriented perspective, emphasising individual agency, positive influences, and socioeconomic considerations. The findings underscore the urgent need for universities and actuarial science programmes to implement targeted support mechanisms addressing the unique challenges black actuarial science students face. The study advocates for increased racial representation, linguistic inclusivity, and socioeconomic equity within actuarial science, highlighting the importance of fostering a supportive, inclusive learning environment. Furthermore, it urges academic institutions to invest in mental health services to alleviate the emotional toll associated with actuarial science studies.